A critical ethnography of communication processes involving the management of oral chemotherapeutic agents by patients with a primary diagnosis of colorectal cancer: study protocol. (10th November 2014) - Mitchell, Gary; Porter, Sam; Manias, Elizabeth
Abstract: Aim: To describe the protocol used to examine the processes of communication between health professionals, patients and informal carers during the management of oral chemotherapeutic medicines to identify factors that promote or inhibit medicine concordance. Background: Ideally communication practices about oral medicines should incorporate shared decision‐making, two‐way dialogue and an equality of role between practitioner and patient. While there is evidence that healthcare professionals are adopting these concordant elements in general practice there are still some patients who have a passive role during consultations. Considering oral chemotherapeutic medications, there is a paucity of research about communication practices which is surprising given the high risk of toxicity associated with chemotherapy. Design: A critical ethnographic design will be used, incorporating non‐participant observations, individual semi‐structured and focus‐group interviews as several collecting methods. Methods: Observations will be carried out on the interactions between healthcare professionals (physicians, nurses and pharmacists) and patients in the outpatient departments where prescriptions are explained and supplied and on follow‐up consultations where treatment regimens are monitored. Interviews will be conducted with patients and their informal carers. Focus‐groups will be carried out with healthcare professionals at the conclusion of the study. These several will be analysed using thematic analysis. This research is funded by the Department for Employment and Learning in Northern Ireland (Awarded February 2012). Discussion: Dissemination of these findings will contribute to the understanding of issues involved when communicating with people about oral chemotherapy. It is anticipated that findings will inform education, practice and policy.